Flexural behaviour of precast segmental concrete beams internally prestressed with unbonded CFRP tendons under four-point loading. (1st August 2018) - Le, Tan D.; Pham, Thong M.; Hao, Hong; Hao, Yifei
Highlights: This is the first time FRP tendons are used in precast segmental beams (PSBs). Strength reduction of FRP tendons is investigated for this new application. Effect of type of joint on structural behaviour of PSBs. Behaviour of PSBs with unbonded FRP tendons. Abstract: This study investigates the use of carbon fibre reinforced polymer (CFRP) tendons on precast segmental beams (PSBs) to tackle the corrosion problems which are likely to occur at joint locations of PSBs prestressed with steel tendons. Up to date, the use of CFRP tendons was extensively documented for monolithic beams while their application on PSBs has not been reported yet. Three precast segmental T-section beams including two beams with unbonded CFRP and one with steel tendons were built and tested under four-point loads in this study. The test results showed that CFRP tendons can be well used to replace the steel tendons on PSBs. The beams with CFRP tendons demonstrated both high strength and high ductility as compared to the beam with steel tendons. However, the stresses in the unbonded CFRP tendons at ultimate loading conditions of the tested beams were low, ranging from only about 66% to 72% of the nominal breaking tensile strength. The type of joints i.e. dry and epoxied, greatly affects the initial stiffness of the beams but has no effect on the opening of joints at ultimate loading stage. Moreover, a comprehensive examination on four existing code equations to predict the stress in the unbonded tendons showed that the four examined codes predicted well the stress at the ultimate loading condition of the unbonded steel tendons, however, they significantly under predicted those in the CFRP tendons. A modification in the strain reduction coefficient used by ACI 440.4R for predicting the stress increment in unbonded CFRP tendons of monolithic beams is therefore proposed for PSBs based on the experimental results.